2011
DOI: 10.1556/comec.12.2011.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of bivalves in relation to environmental conditions (middle Danube catchment, Hungary)

Abstract: The spatial distribution of bivalves in relation to environmental conditions was studied along a second-and third order stream-medium-sized river (River Ipoly)-large river (River Danube) continuum in the Hungarian Danube River system. Quantitative samples were collected four times in 2007 and a total of 1662 specimens, belonging to 22 bivalve species were identified. Among these species, two are endangered (Pseudanodonta complanata, Unio crassus) and five are invasive (Dreissena polymorpha, D. rostriformis bug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 43 publications
1
26
0
1
Order By: Relevance
“…Therefore, the association between pulmonate species, S. corneum and macrophytes in the Wkra River catchment area may be explained by their feeding mode and the filtration process. This result is consistent with the survey done by BódIs et al (2011) who, based on a CCA analysis, showed a positive correlation between the distribution of S. corneum or other fingernail clams and the macrophyte occurrence.…”
Section: Mollusc Communities In Relation Tosupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, the association between pulmonate species, S. corneum and macrophytes in the Wkra River catchment area may be explained by their feeding mode and the filtration process. This result is consistent with the survey done by BódIs et al (2011) who, based on a CCA analysis, showed a positive correlation between the distribution of S. corneum or other fingernail clams and the macrophyte occurrence.…”
Section: Mollusc Communities In Relation Tosupporting
confidence: 92%
“…The mean density of the depressed river mussel was lower than 0.4 indiv. m -2 in the middle Danube catchment area in Hungary (BódIs et al 2011). The range of P. complanata extends across most European countries: Finland, Sweden, Russia, Germany, Austria, Switzerland, France, the Netherlands and the United Kingdom.…”
Section: Rare Threatened and Alien Species In The Mollusc Communitiementioning
confidence: 98%
See 2 more Smart Citations
“…However, "suspension feeders" presented their highest number of individuals in the outermost part of the lagoon where hydrodynamics ranged from moderate to high. It has previously been shown that the dominance of this trophic group is determined by hydrodynamics (Sanz 1986, Pearson and Rosenberg 1987, Bódis et al 2011) and the sediment grain size (Sanders 1958, Young and Rhoads 1971, Jaramillo 1984, Probert 1984. Concerning "carnivores", they reached their maximal proportion at the outer part of Papapouli Lagoon (ST3) as well as in station ST1, especially in winter and spring where the sea-inlet was open.…”
Section: Discussionmentioning
confidence: 98%